To Recognize Indication of Financial Distress and Or Bankruptcy of Five Textile Company for Five Years Period Using Five Financial Distress Models - Usmansyah Usmansyah; Pudjiastuty Pudjiastuty (Return : Study of Management, Economic and Bussines, 2023)
Background: In a business, risk of profit and loss is an inevitability. Every company have their own ways to mitigate those risk, prepare a proper treatment, and other efforts get the predetermined purpose, that is profit. Serious risk and its consequences can bring company into financial distress, and in the next step can become bankrupt. The Indications of it can be seen from the financial performance of the companies. Aim: To find out whether a company engaged in the textile and textile products sector is in serious financial difficulty which could have implications for bankruptcy, several theories have been developed. This study is to analyze indication of financial distress and its possibility to become bankrupt. The study is using financial data of five textile and textile product companies listed on the Indonesia Stock Exchange for five years of 2017 – 2021, using five models of Analysis of Financial Distress, that are Zmijewski Model, Fulmer Model, Grover Model, Altman Z-Score Model, and Springate Model. Method: This study uses secondary data on the textile companies listed on the Indonesia Stock Exchange. The sample used in this study were five companies. The sample selection uses purposive sampling. This type of research used in this research is quantitative descriptive, namely research on problems in the form of the current facts of a population. Testing research data using data analysis of model financial distress. Findings: This study uses secondary data on the textile companies listed on the Indonesia Stock Exchange. The sample used in this study were five companies. The sample selection uses purposive sampling. This type of research used in this research is quantitative descriptive, namely research on problems in the form of the current facts of a population. Testing research data using data analysis of model financial distress.